Comparing plastic ingestion in juvenile and adult stranded short-tailed shearwaters (Puffinus tenuirostris) in eastern Australia - Acampora, H; Schuyler, QA; Townsend, KA; Britta Hardesty (2014)
Numerous species of seabirds have been shown to ingest anthropogenic debris, but few studies have compared ingestion rates between adults and juveniles of the same species. We investigated marine debris ingestion by short-tailed shearwaters ( Puffinus tenuirostris ) obtained through two stranding events on North Stradbroke Island, Australia in 2010 (n= 102; adult) and 2012 (n= 27; juveniles). Necropsies were conducted and solid contents found in guts were categorized into type and color. Over 67% of birds ingested anthropogenic debris: 399 pieces of debris were identified. We found no significant relationship between body condition of birds which had ingested anthropogenic debris and those that had not. Juvenile birds were more likely to ingest debris than were adult birds and juveniles ingested significantly more pieces of debris than did adults. Male and female birds ingested similar amounts and weights of debris. To determine if P. tenuirostris actively selects for certain types of debris, we compared ingested debris to samples obtained from boat-based tows. Significant differences were found, suggesting that the birds select for hard plastic, rubber and balloons.